Healable network polymers bearing flexible poly(Lauryl Methacrylate) chains via thermo-reversible furan-maleimide diels-alder reaction - Patil, Sachin S.; Torris, Arun; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
A new ATRP initiator containing two furyl rings, namely, bis(furan-2-ylmethyl) 2-bromopentanedioate was synthesized starting from commercially available L-glutamic acid as a precursor. Well-defined bisfuryl-terminated poly(lauryl methacrylate) macromonomers with molecular weight and dispersity in the range 5000-12,000 g mol(-1) and 1.30-1.37, respectively, were synthesized employing the initiator by atom transfer radical polymerization (ATRP). Independently, 1,1',1"(nitrilotris(ethane-2,1-diyl)) tris(1H-pyrrole-2,5-dione) was synthesized as a tris-maleimide counterpart for furan-maleimide click reaction. Thermo-reversible network polymer bearing flexible poly(lauryl methacrylate; (PLMA) chains was obtained by furan-maleimide Diels-Alder click reaction of bisfurylterminated PLMA with 1,1',1"-(nitrilotris(ethane-2,1-diyl)) tris(1Hpyrrole-2,5-dione). The prepared network polymer showed retro-Diels-Alder reaction in the temperature range 110-170 degrees C as determined from DSC analysis. The presence of low Tg (-40 degrees C) PLMA chains induced chain mobility to the network structure which led to the complete scratch healing of the coating at 60 degrees C in five days due to furan-maleimide adduct formation. The storage modulus of the network polymer was found to be 3.7 x 10(4) Pa at the constant angular frequency of 5 rad/ sec and strain of 0.5%. The regular reversal of storage (G0) and loss modulus (G") was observed with repeated heating (40 to 110 degrees C) and cooling cycles (110 to 40 degrees C) at constant angular frequency and strain. (C) 2017 Wiley Periodicals, Inc.
Keywords: ethane; Monomers; polymerization

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes